Analysis of Leader-Member Exchange toward Organizational Commitment, Job Satisfaction, Job Performance: Is Virtual Work Moderating? - Depta Berliantarest Hirnawati; Handrio Adhi Pradana (Journal of Business and Management Review, 2023)
The aim of this research is to examine relationship between leader member exchange (LMX), organizational commitment, job satisfaction, and job performance with moderating mechanism of virtual work. This research was an explanatory-quantitative approach to explain the effects of LMX toward organizational commitment, job satisfaction, and job performance during pandemic specific in the context of Islamic college. This research had a total of 108 respondents that consisted of both educational staffs and lecturers from various faculties including Faculty of Business and Economics, Law, Medicine, Industrial Engineering, Psychology and Socio-Culture, Islamic Religious Science, Civil Engineering and Planning, Mathematics and Nature. This study was conducted in one of well-known private Islamic higher education in Yogyakarta. The result of this study explained that LMX had a positive significant effect on organizational commitment, job satisfaction, and job performance. However, the authors found that virtual work was only able to moderate the effect of LMX on organizational commitment and was unable to moderate the relationship of LMX, job satisfaction, and job performance. A more detailed sentences are stated in discussion and implication section of this article.